PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN REMAJA TENTANG PENYAKIT HIV/AIDS DI SMKS X JAKARTA - Nurlindawati; Kustia Anggereni; Djimmy Heru Purnomo Babo; Tri Yunita (LPPM Institut Sains dan Kesehatan Bone, 2023)
Abstract. Adolescence is a productive age that is very vulnerable to contracting HIV-AIDS, because at that time adolescents experience high sexual urges and are always looking for information about sex, and the knowledge and information related to reproductive health they get is very lacking. Teenagers generally prefer to look for various sources of information they can get, such as accessing adult sites on the internet, trying to masturbate, making out or even having sex with their girlfriends. Health education plays an important role in increasing youth's knowledge and attitudes towards HIV-AIDS prevention. The purpose of this study was to determine the effect of health education on increasing adolescent knowledge about HIV/AIDS. The type of research used is qualitative with a pre-experimental design with one group pretest posttest. The results of this study indicated that there was an effect of health education on increasing adolescent knowledge about HIV/AIDS in class XII students of SMKS X Jakarta with the chi-square test results obtained p-value = 0.000.